Knowledge, Attitude and Practices towards COVID-19 Vaccine in Pregnant and Postpartum Women: A Cross-sectional Study - Nupur Mandar Deshpande; Rohan Udayan Patwardhan; Shilpa Nitin Chaudhari (Journal of Clinical and Diagnostic Research, 2023)
Introduction: Pregnant and lactating women have been included in the ongoing vaccination drive against Coronavirus Disease 2019 (COVID-19) by the Government of India. Despite the fact, the vaccination rates among this particular group were fairly dismal. Aim: To study the Knowledge, Attitude and Practices (KAP) related to the COVID-19 vaccine in pregnant and postpartum women in a tertiary care hospital. Materials and Methods: This cross-sectional study was conducted in Obstetrics and Gynaecology wards and Outpatient Department, Smt. Kashibai Navale Medical College and General Hospital (tertiary care hospital), Pune, Maharashtra, India, from August 2021 to October 2021 among 251 pregnant and postpartum patients. The data was collected using a face-to-face questionnaire. The questionnaire included demographic characteristics of study participants and a set of questions to test the KAP towards COVID-19 vaccination in pregnancy. Results: A total of 251 pregnant and postpartum women, with a mean age of 24.54 years, were surveyed. Among all the participants, 223 (89.92%) knew about the existence of the COVID-19 vaccine, however, only 23 (9.16%) were vaccinated. The most common reasons for refusing the vaccine were concerns for their own safety (n=39, 17.5%) or that of the foetus (n=107, 48.1%), lack of awareness (58.5%), and lack of recommendation by healthcare workers (63.5%). Only 67.8% of subjects believed in the efficacy of the vaccine. Overall, 16 (9.41%) women with no history of miscarriages or abortions had taken the vaccine, whereas, seven (9.33%) participants with a history of miscarriage or abortions had taken the vaccine. Conclusion: The present study reported low acceptance of the COVID-19 vaccine in pregnant and postpartum women. Lack of awareness and concern for vaccine safety were the major reasons for this. Recognising the major reasons for vaccine hesitancy among this population will be useful for creating effective strategies to increase vaccine acceptance during this pandemic.